ANALISIS SISTEM INFORMASI AKUNTANSI UNTUK MENINGKATKAN MUTU PELAYANAN DAN EFEKTIVITAS PENAGIHAN DANA PEMBAYARAN KLAIM BPJS - Iqbal Fahreza (2020)
This study is an qualified research with an ethometodological approach that imposed to an antidote system of accounting information used by RSAU dr. Esnawan Antariksa Based on aspects of the patient's BPJS service and aspects of funds funds claim BPJS that it may identify the effectiveness in an usage of accounting information systems. With a technique technique of data - Interview, paperwork documents, observation and perform of group discussions. This research results show RSAU dr. Esnawan Antariksa that Has used technology infrastructure as well as following modern times, other than that accounting information is integraed to other departments. But this long claim will be a challenge for the hospital, considering the hospital has limited human resources, such as staff Verificator, staff input data patient, Because patient care activities cannot be determined how many patients will come, this long flow of service will be the identification of impacts or threats and weaknesses of internal control because of using Accounting system information.